Talazoparib Does Not Interact with ABCB1 Transporter or Cytochrome P450s, but Modulates Multidrug Resistance Mediated by ABCC1 and ABCG2: An in Vitro and Ex Vivo Study - Sabet, Ziba; Vagiannis, Dimitrios; Budagaga, Youssif; Zhang, Yu; Novotná, Eva; Hanke, Ivo; Rozkoš, Tomáš; Hofman, Jakub (International journal of molecular sciences, 2022)
Talazoparib (Talzenna) is a novel poly (adenosine diphosphate-ribose) polymerase (PARP) inhibitor that is clinically used for the therapy of breast cancer. Furthermore, the drug has shown antitumor activity against different cancer types, including non-small cell lung cancer (NSCLC). In this work, we investigated the possible inhibitory interactions of talazoparib toward selected ATP-binding cassette (ABC) drug efflux transporters and cytochrome P450 biotransformation enzymes (CYPs) and evaluated its position in multidrug resistance (MDR). In accumulation studies, talazoparib interacted with the ABCC1 and ABCG2 transporters, but there were no significant effects on ABCB1. Furthermore, incubation assays revealed a negligible capacity of the tested drug to inhibit clinically relevant CYPs. In in vitro drug combination experiments, talazoparib synergistically reversed daunorubicin and mitoxantrone resistance in cells with ABCC1 and ABCG2 expression, respectively. Importantly, the position of an effective MDR modulator was further confirmed in drug combinations performed in ex vivo NSCLC patients-derived explants, whereas the possible victim role was refuted in comparative proliferation experiments. In addition, talazoparib had no significant effects on the mRNA-level expressions of MDR-related ABC transporters in the MCF-7 cellular model. In summary, our study presents a comprehensive overview on the pharmacokinetic drug-drug interactions (DDI) profile of talazoparib. Moreover, we introduced talazoparib as an efficient MDR antagonist.
Keywords: P-glykoproteiny; nádorové proteiny; Neoplasm Proteins; Drug Resistance, Multiple; mnohočetná léková rezistence; ATP Binding Cassette Transporter, Subfamily G, Member 2; ATP Binding Cassette Transporter, Subfamily B; ABC transportéry; systém (enzymů) cytochromů P-450; lidé; nádory plic; Carcinoma, Non-Small-Cell Lung; Cytochrome P-450 Enzyme System; ABC transportér z rodiny G, člen 2; nemalobuněčný karcinom plic; Humans; Lung Neoplasms; ATP-Binding Cassette Transporters